PENGARUH K3 DAN LINGKUNGAN TERHADAP PERSEPSI KARYAWAN SERTA DAMPAKNYA PADA KEPUASAN KERJA DI PT PLN (PERSERO) ULP SAMBAS - Dina Ilham Nurjanah; Sri Deti; Zulkan (Cross-Border Journal of Business Management, 2026)
This study aims to examine employees’ perceptions of the implementation of Occupational Safety and Health (OSH) and the work environment, as well as their effects on job satisfaction at PT PLN (Persero) Unit Layanan Pelanggan (ULP) Sambas. This research is motivated by the importance of implementing OSH and creating a safe and comfortable work environment to support employee job satisfaction, particularly in the electricity sector, which is characterized by relatively high occupational risks. This study employs a quantitative approach with a descriptive design and multiple linear regression analysis. The research data were collected through questionnaires distributed to 50 respondents consisting of permanent employees and employees of subsidiary companies at PT PLN (Persero) ULP Sambas. The data analysis techniques include validity testing, reliability testing, partial testing (t-test), simultaneous testing (F-test), and coefficient of determination analysis. The results indicate that employees’ perceptions of OSH implementation and the work environment are in the good category. The partial test results show that perceptions of OSH implementation and the work environment each have a positive and significant effect on job satisfaction, with significance values of 0.001 for OSH and 0.003 for the work environment, both of which are less than 0.05. The simultaneous test results indicate that both variables jointly have a significant effect on employee job satisfaction, with a significance value of 0.000. The coefficient of determination (Adjusted R Square) of 0.280 indicates that 28% of the variation in employee job satisfaction can be explained by employees’ perceptions of OSH implementation and the work environment, while the remaining percentage is influenced by other variables not examined in this study